Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1111/jdv.12975
|View full text |Cite
|
Sign up to set email alerts
|

Tertiary individual prevention improves mental health in patients with severe occupational hand eczema

Abstract: Our data underscore the importance of psychological interventions in addition to dermatological treatment in the framework of prevention measures for OHE. These measures should be applied at an early stage of OHE prior to the occurrence of sick leave.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 27 publications
0
15
0
2
Order By: Relevance
“…From the 369 articles identified in the literature search, 328 were excluded based on the exclusion criteria, leaving 41 publications for the final analysis 12‐52 . The list of included publications and their characteristics are given in Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the 369 articles identified in the literature search, 328 were excluded based on the exclusion criteria, leaving 41 publications for the final analysis 12‐52 . The list of included publications and their characteristics are given in Table .…”
Section: Resultsmentioning
confidence: 99%
“…For example, a study aimed to assess the efficacy of four weeks of 0.05% halometasone monohydrate in patients with occupational irritant and allergic contact dermatitis demonstrated significant improvement of QoL at week four 44 . Other studies on occupational skin diseases had follow‐up periods from three weeks to five years 12,13,15,17,18,25,35,39,42,45,47,52 . Significant QoL improvement was observed three weeks after a tertiary individual prevention programme that included dermatological therapy, detailed healthcare instruction and psychological treatment 13 …”
Section: Resultsmentioning
confidence: 99%
“…11 Although our findings suggest there is no direct causal effect of onset of allergic disease on the onset of mental health phenotypes, there is some evidence that effectively treating skin disease can improve mental well-being. 41,42 A recent report by the All-Party Parliamentary Group on Skin has recommended that patients with a chronic skin condition should receive an annual assessment of the psychological impact of their condition. 43 In our study, the genetic instruments we used were identified in GWAS which looked at the onset of allergic disease or mental health phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Hand eczema in healthcare workers may promote the carriage of microorganisms on eczematous skin before transmission to patients (12,13). Healthcare workers have been shown to benefit from skin-care education and individual counseling (14) and in Denmark and Germany an evidencebased skin protection program has been carried out in hospitals (15)(16)(17)(18). While the prevalence rate of hand eczema in Harbin, Zhenjiang and Shijiazhuang cities has been reported to be 20% (19), 17.7% (20), and 22.3% (21) respectively, there is little data on its prevalence in health care workers, possibly because little attention is paid to the disease.…”
Section: Original Articlementioning
confidence: 99%